1992
DOI: 10.2136/sssaj1992.03615995005600020016x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Naturally Occurring Dissolved Organic Carbon in Laboratory Columns Containing Aquifer Material

Abstract: The subsurface transport of ionic and nonionic pollutants may be strongly impacted by the movement of naturally occurring dissolved organic carbon (DOC) in aquifers. Thus, the adsorption, desorption, and transport of DOC in laboratory columns containing well‐packed aquifer material was investigated. Data showed that the breakthrough of DOC from aquifer columns was the result of complex adsorption reactions between DOC and the aquifer material. Breakthrough curves (BTCs) of the DOC were characterized by an init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 0 publications
11
70
0
Order By: Relevance
“…3). Dunnivant et al (58) suggested that leaching of TOC can be delayed with an extended tail due to slow and nonlinear adsorption to soil particles, but the sorption capacity of the sandy loam soil used for this experiment was moderate, as indicated by a cation exchange capacity of 13.1 cmol kg Ϫ1 in the low layer of this soil (28). The electrical conductivities (EC) of leachates from LS and OLS treatments were higher than RS during IE2 to IE4.…”
Section: Resultsmentioning
confidence: 83%
“…3). Dunnivant et al (58) suggested that leaching of TOC can be delayed with an extended tail due to slow and nonlinear adsorption to soil particles, but the sorption capacity of the sandy loam soil used for this experiment was moderate, as indicated by a cation exchange capacity of 13.1 cmol kg Ϫ1 in the low layer of this soil (28). The electrical conductivities (EC) of leachates from LS and OLS treatments were higher than RS during IE2 to IE4.…”
Section: Resultsmentioning
confidence: 83%
“…Two potential mechanisms for DOC release during the desorption experiments include (i) actual desorption from surface binding sites on sediment/sand particles and (ii) release associated with POC decomposition. There is ample evidence for sorption of DOC to soil and sediment particle surfaces (3,(42)(43)(44)(45)(46) and for the release of sorbed DOC during hydrologic disturbance (47)(48)(49). Numerous studies have documented the release of DOC during POC decomposition in soils and sediments (e.g., see references 50-56).…”
Section: Discussionmentioning
confidence: 99%
“…In this, the field experiment was successful. While column studies using site-specific material [Dunnivant et al, 1992a] demonstrated differences in the mobility of NOM subcomponents, a singlespecies solute model could reproduce the NOM breakthrough curve over the short times and distances of the column studies [Jardine et al, 1992]. The larger scale of the field experiment clarified the importance of the multicomponent nature of NOM transport: the mobile components of NOM could be better characterized in the larger-volume field samples, and the spatial and temporal scale of the field experiment demonstrated the conceptual and operational failure of single-species solute models more conclusively than did the results of the column studies.…”
Section: Discussionmentioning
confidence: 99%